Interdisciplinary Discourse : Communicating Across Disciplines - Choi, Seongsook; Richards, Keith (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book uncovers exactly what is involved when researchers from different disciplines engage with one another in research projects. The authors identify the opportunities and difficulties involved in interdisciplinary engagement, and challenge current claims about where the greatest difficulties are to be found. The first part of the book introduces interdisciplinarity and identifies key issues that influence our understanding of it. The second part of the book presents the findings of research based on over 50 hours of recording and nearly 450,000 words of transcript drawn from a number of university faculties, concluding with a discussion of how this might inform interdisciplinary practice. The book is accessible to the non-specialist reader while also being of interest to social scientists working in professional and academic communication. Seongsook Choi is a lecturer in the Moray House School of Education, University of Edinburgh, UK. Her current research focuses on interdisciplinary talk, the development of analytical tools for mapping interactional patterns, and representing these dynamically in visual formats. Keith Richards worked at the Universities of Aston and Warwick, UK, but is now retired. His publications include Qualitative Inquiry in TESOL, Language and Professional Identity, and Research Methods for Applied Language Studies (with Steven Ross and Paul Seedhouse).- Resumé vydavatel